3D-Bioprinted Urinary Catheters Enable Sustained Probiotic Recovery Under Flow and Improve Bladder Colonization In Vivo - Anthony J. Kyser; Arielle Greiner; Victoria Harris; Rudra Patel; Hermann B. Frieboes; Nicole M. Gilbert (Probiotics and Antimicrobial Proteins, 2025)

Rugged LC-MS/MS method for the large-scale monitoring of glyphosate and other highly polar pesticides in soils across European Union olive orchards - Alfonso Fernández-García; David Moreno-González; Andrés J. Rascón; Ana B. Martínez-Piernas; Bienvenida Gilbert-López; Antonio J. Manzaneda; Juan F. García-Reyes (Environmental Pollution, 2025)

The potential of oviduct tags and fine‐scale acoustic telemetry to reveal the timing and location of spawning in Arctic salmonids ( Salvelinus spp.) - Véronique Dubos; Les N. Harris; Richard Ekpakohak; Brendan K. Malley; Matthew J. H. Gilbert; Nathan B. Furey; Jean‐Sébastien Moore (Journal of Fish Biology, 2025)
Identifying and characterizing spawning locations are paramount for the protection of critical fish habitats but can be challenging, particularly in remote locations. Using the underexplored oviduct‐tagging technique, we aimed to identify the timing and location of spawning for wild Arctic char ( Salvelinus alpinus ) and lake trout ( Salvelinus namaycush ) in two high‐Arctic lakes in Nunavut. Specifically, Innovasea V7 acoustic telemetry transmitters were inserted into the oviducts of 13 Arctic char and 4 lake trout, and the timing and location of tag expulsion were determined using a fine‐scale positioning system. Twenty Arctic char and 20 lake trout were also tagged with abdominal V16 transmitters, and 10 of them were paired with the oviduct tags, to further study the behavior of individual fish during the spawning season. Oviduct tags from four Arctic char and one lake trout could be used to assess the timing and location of spawning. Spawning anadromous Arctic char drastically reduced their activity and remained proximate to their presumed spawning location immediately before and for months after spawning. In contrast, a non‐anadromous (i.e., freshwater resident) Arctic char and a lake trout showed little to no reduction in activity around presumed spawning events. Because of the highlighted sedentary behavior of inferred spawning anadromous Arctic char implanted with both abdominal and oviduct tags, we could also infer potential spawning based on the behavior of individuals equipped only with abdominal tags. Spawning areas identified via telemetry also aligned well with Inuit knowledge of those lakes. This is the first field study to use acoustic oviduct and abdominal tags coupled with a fine‐scale positioning system. Despite a limited success rate of ejection, the study reveals the strong potential of the method to study spawning habitat and timing, particularly in remote areas.

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Host Species–Microbiome Interactions Contribute to Sphagnum Moss Growth Acclimation to Warming - Tatjana Živković; Alyssa A. Carrell; Gustaf Granath; A. Jonathan Shaw; Dale A. Pelletier; Christopher W. Schadt; Dawn M. Klingeman; Mats B. Nilsson; Manuel Helbig; Denis Warshan; Ingeborg J. Klarenberg; Daniel Gilbert; et al. (Global Change Biology, 2025)
Sphagnum moss is the dominant plant genus in northern peatlands responsible for long‐term carbon accumulation. Sphagnum hosts diverse microbial communities (microbiomes), and its phytobiome (plant host + constituent microbiome + environment) plays a key role in nutrient acquisition along with carbon cycling. Climate change can modify the Sphagnum ‐associated microbiome, resulting in enhanced host growth and thermal acclimation as previously shown in warming experiments. However, the extent of microbiome benefits to the host and the influence of host–microbe specificity on Sphagnum thermal acclimation remain unclear. Here, we extracted Sphagnum microbiomes from five donor species of four peatland warming experiments across a latitudinal gradient and applied those microbiomes to three germ‐free Sphagnum species grown across a range of temperatures in the laboratory. Using this experimental system, we test if Sphagnum 's growth response to warming depends on the donor and/or recipient host species, and we determine how the microbiome's growth conditions in the field affect Sphagnum host growth across a range of temperatures in the laboratory. After 4 weeks, we found that the highest growth rate of recipient Sphagnum was observed in treatments of matched host–microbiome pairs, with rates approximately 50% and 250% higher in comparison to maximum growth rates of non‐matched host–microbiome pairs and germ‐free Sphagnum , respectively. We also found that the maximum growth rate of host–microbiome pairs was reached when treatment temperatures were close to the microbiome's native temperatures. Our study shows that Sphagnum 's growth acclimation to temperature is partially controlled by its constituent microbiome. Strong Sphagnum host–microbiome species specificity indicates the existence of underlying, unknown physiological mechanisms that may drive Sphagnum 's ability to acclimatize to elevated temperatures. Together with rapid acclimation of the microbiome to warming, these specific microbiome–plant associations have the potential to enhance peatland resilience in the face of climate change.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Evaluation of contingency actions to control the spread of raccoon rabies in Ohio and Virginia - Amy J. Davis; Richard B. Chipman; Kathleen M. Nelson; Betsy S. Haley; Jordona D. Kirby; Xiaoyue Ma; Ryan M. Wallace; Amy T. Gilbert (Preventive Veterinary Medicine, 2024)

Expert-driven play Fairway Analysis applied to the Azufral Volcano Geothermal Area in southwestern Colombia - Emmanuel Olvera-García; Bridget F. Ayling; Jesús B. Rueda-Gutiérrez; Anieri M. Morales Rivera; Gilbert F. Rodríguez-Rodríguez; Jaison Malo; Jefferson Sánchez; Yeimy Rodríguez-Molina; Yerson Pardo; Yenny P. Casallas-Veloza; J. Camilo Matiz-León; Gina Rodríguez-Ospina; et al. (Geothermics, 2023)

Multi-timescale dynamics of extreme river flood and storm surge interactions in relation with large-scale atmospheric circulation: Case of the Seine estuary - E.I. Turki; J. Deloffre; N. Lecoq; R. Gilbert; E.T. Mendoza; B. Laignel; E. Salameh; A.D. Gutierrez Barcelo; M. Fournier; N. Massei (Estuarine, Coastal and Shelf Science, 2023)

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Interspecific oral rabies vaccine bait competition in the Southeast United States - Wesley C. Dixon; Jacob E. Hill; Richard B. Chipman; Amy J. Davis; Amy T. Gilbert; James C. Beasley; Olin E. Rhodes; Guha Dharmarajan (Applied Animal Behaviour Science, 2023)

Effects of ants on riparian poplars: an ex situ experiment of biotic interaction - D. Corenblit; B. Corbara; R. Cereghino; A. Dejean; P. Duran; V. Garófano-Gómez; F. Gilbert; E. González-Sargas; F. Julien; L. Lambs; C. Mainguin; L. Mazal; et al. (Arthropod-Plant Interactions, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Sorbents for treatment of hereditary hemochromatosis - Anna Wilson; Leslie Laguna; Lansten Yew; Kerry Kao; Kathryn Bauguess; Jiaying Wang; Sofia de la O; Grant Romme; William Gilbert; Ana Rita C. Morais; Jian Qian; Cory J. Berkland; et al. (Medicinal Chemistry Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Using DNA to distinguish between faeces of Dugong dugon and Chelonia mydas: non-invasive sampling for IUCN-listed marine megafauna - S. J. Tol; M. Harrison; R. Groom; J. Gilbert; D. Blair; R. Coles; B. C. Congdon (Conservation Genetics Resources, 2021)

EXPRESSION OF CONCERN: InsectChange: a global database of temporal changes in insect and arachnid assemblages - Roel van Klink; Diana E. Bowler; Orr Comay; Michael M. Driessen; S. K. Morgan Ernest; Alessandro Gentile; Francis Gilbert; Konstantin B. Gongalsky; Jennifer Owen; Guy Pe'er; Israel Pe'er; Vincent H. Resh; et al. (Ecology, 2021)
Insects are the most ubiquitous and diverse group of eukaryotic organisms on Earth, forming a crucial link in terrestrial and freshwater food webs. They have recently become the subject of headlines because of observations of dramatic declines in some places. Although there are hundreds of long‐term insect monitoring programs, a global database for long‐term data on insect assemblages has so far remained unavailable. In order to facilitate synthetic analyses of insect abundance changes, we compiled a database of long‐term (≥10 yr) studies of assemblages of insects (many also including arachnids) in the terrestrial and freshwater realms. We searched the scientific literature and public repositories for data on insect and arachnid monitoring using standardized protocols over a time span of 10 yr or longer, with at least two sampling events. We focused on studies that presented or allowed calculation of total community abundance or biomass. We extracted data from tables, figures, and appendices, and, for data sets that provided raw data, we standardized trapping effort over space and time when necessary. For each site, we extracted provenance details (such as country, state, and continent) as well as information on protection status, land use, and climatic details from publicly available GIS sources. In all, the database contains 1,668 plot‐level time series sourced from 165 studies with samples collected between 1925 and 2018. Sixteen data sets provided here were previously unpublished. Studies were separated into those collected in the terrestrial realm (103 studies with a total of 1,053 plots) and those collected in the freshwater realm (62 studies with 615 plots). Most studies were from Europe (48%) and North America (29%), with 34% of the plots located in protected areas. The median monitoring time span was 19 yr, with 12 sampling years. The number of individuals was reported in 129 studies, the total biomass was reported in 13 studies, and both abundance and biomass were reported in 23 studies. This data set is published under a CC‐BY license, requiring attribution of the data source. Please cite this paper if the data are used in publications, and respect the licenses of the original sources when using (part of) their data as detailed in Metadata S1: Table 1.

Arsenic Exposure in Relation to Apple Consumption Among Infants in the New Hampshire Birth Cohort Study - A. J. Signes-Pastor; T. Punshon; K. L. Cottingham; B. P. Jackson; V. Sayarath; D. Gilbert-Diamond; S. Korrick; M. R. Karagas (Exposure and Health, 2020)

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Detecting spiny dogfish in grey seal diets - Kathryn A. Ono; Cathleen M. Steinbeiser; Austin B. Coco; Matthew J. Sheehan; Abigail J. Beck; Michelle N. Dufault; Katelyn M. Gilbert; Jessica J. Antonez; Zachary H. Olson (Conservation Genetics Resources, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

The role of substrate holding in achieving critical swimming speeds: a case study using the invasive round goby (Neogobius melanostomus) - Matthew J. H. Gilbert; Janelle M. Barbarich; Matthew Casselman; Ashley V. Kasurak; Dennis M. Higgs; Keith B. Tierney (Environmental Biology of Fishes, 2016)

Overview and modeling of mechanical and thermomechanical impact of underground coal gasification exploitation - F. Laouafa; R. Farret; S. Vidal-Gilbert; J-B. Kazmierczak (Mitigation and Adaptation Strategies for Global Change, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Lemming winter habitat choice: a snow-fencing experiment - Donald G. Reid; Frédéric Bilodeau; Charles J. Krebs; Gilles Gauthier; Alice J. Kenney; B. Scott Gilbert; Maria C.-Y. Leung; David Duchesne; Elizabeth Hofer (Oecologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Natural outbreak of Streptococcus agalactiae (GBS) infection in wild giant Queensland grouper, Epinephelus lanceolatus (Bloch), and other wild fish in northern Queensland, Australia - R O Bowater; J Forbes‐Faulkner; I G Anderson; K Condon; B Robinson; F Kong; G L Gilbert; A Reynolds; S Hyland; G McPherson; J O’ Brien; D Blyde (Journal of Fish Diseases, 2012)
Ninety‐three giant Queensland grouper, Epinephelus lanceolatus (Bloch), were found dead in Queensland, Australia, from 2007 to 2011. Most dead fish occurred in northern Queensland, with a peak of mortalities in Cairns in June 2008. In 2009, sick wild fish including giant sea catfish, Arius thalassinus (Rüppell), and javelin grunter, Pomadasys kaakan (Cuvier), also occurred in Cairns. In 2009 and 2010, two disease epizootics involving wild stingrays occurred at Sea World marine aquarium. Necropsy, histopathology, bacteriology and PCR determined that the cause of deaths of 12 giant Queensland grouper, three wild fish, six estuary rays, Dasyatis fluviorum (Ogilby), one mangrove whipray, Himantura granulata (Macleay), and one eastern shovelnose ray, Aptychotrema rostrata (Shaw), was Streptococcus agalactiae septicaemia. Biochemical testing of 34 S. agalactiae isolates from giant Queensland grouper, wild fish and stingrays showed all had identical biochemical profiles. The 16S rRNA gene sequences of isolates confirmed all isolates were S. agalactiae ; genotyping of selected S. agalactiae isolates showed the isolates from giant Queensland grouper were serotype Ib, whereas isolates from wild fish and stingrays closely resembled serotype II. This is the first report of S. agalactiae from wild giant Queensland grouper and other wild tropical fish and stingray species in Queensland, Australia.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Environmental Radioxenon Levels in Europe: a Comprehensive Overview - Paul R. J. Saey; Clemens Schlosser; Pascal Achim; Matthias Auer; Anders Axelsson; Andreas Becker; Xavier Blanchard; Guy Brachet; Luis Cella; Lars-Erik De Geer; Martin B. Kalinowski; Gilbert Le Petit; et al. (Pure and Applied Geophysics, 2010)

Mechanical damage to pollen aids nutrient acquisition in Heliconius butterflies (Nymphalidae) - Harald W. Krenn; Monika J. B. Eberhard; Stefan H. Eberhard; Anna-Laetitia Hikl; Werner Huber; Lawrence E. Gilbert (Arthropod-Plant Interactions, 2009)

Can Campylobacter coli induce Guillain-Barré syndrome? - A. van Belkum; B. Jacobs; E. van Beek; R. Louwen; W. van Rijs; L. Debruyne; M. Gilbert; J. Li; A. Jansz; F. Mégraud; H. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Pathogens promote plant diversity through a compensatory response - Devon J. Bradley; Gregory S. Gilbert; Jennifer B. H. Martiny (Ecology Letters, 2008)
Pathogens are thought to promote diversity in plant communities by preventing competitive exclusion. Previous studies have focussed primarily on single‐plant, single‐pathogen interactions, yet the interactions between multiple pathogens and multiple hosts may have non‐additive impacts on plant community composition. Here, we report that both a bacterial and a fungal pathogen maintained the diversity of a four‐species plant community across five generations; however, significant interactions between the pathogens resulted in less plant diversity when the two pathogens were present than when the fungal pathogen was present alone. Standard models predict that pathogens will maintain plant diversity when they cause a disproportionate loss of fitness in the dominant plant species. In our experiment, however, pathogens maintained plant diversity because the rare species produced more seeds through a compensatory response to pathogen infection. Finally, we found that the influence of pathogens on maintaining plant diversity was 5.5 times greater than the influence of nutrient resource heterogeneity. Pathogens may be a major factor in maintaining plant diversity, and our findings emphasize the importance of investigating the roles of pathogens in natural plant communities.

Chromosomal evolution in tenrecs (Microgale and Oryzorictes, Tenrecidae) from the Central Highlands of Madagascar - C. Gilbert; S. M. Goodman; V. Soarimalala; L. E. Olson; P. C. M. O’Brien; F. F. B. Elder; F. Yang; M. A. Ferguson-Smith; T. J. Robinson (Chromosome Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Maternal mosaicism for mutations in the ARX gene in a family with X linked mental retardation - K. Poirier; J. Abriol; I. Souville; C. Laroche-Raynaud; C. Beldjord; B. Gilbert; J. Chelly; T. Bienvenu (Human Genetics, 2005)

Species Richness and Invasion Vectors: Sampling Techniques and Biases - S. Gollasch; H. Rosenthal; H. Botnen; M. Crncevic; M. Gilbert; J. Hamer; N. Hülsmann; C. Mauro; L. McCann; D. Minchin; B. Öztürk; M. Robertson; et al. (Biological Invasions, 2003)

Comparison of Canadian Fusarium graminearum isolates for aggressiveness, vegetative compatibility, and production of ergosterol and mycotoxins - J. Gilbert; D. Abramson; B. McCallum; R. Clear (Mycopathologia, 2002)

Rotavirus assembly – interaction of surface protein VP7 with middle layer protein VP6 - J. M. Gilbert; N. Feng; J. T. Patton; H. B. Greenberg (Archives of Virology, 2001)

Visual discrimination of textures with identical third-order statistics - B. Julesz; E. N. Gilbert; J. D. Victor (Biological Cybernetics, 1978)

Crop and market news - B. A. Brown; H. C. Moore; P. N. Davis; J. F. Sharples; H. O. Werner; O. C. Hicks; J. Gilbert Borton; H. C. Odell; E. V. Hardenburg (American Journal of Potato Research, 1926)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)